Pidotimod for Covid-19 - Miranda Ojeda, Rául; Ávila Yáñez, Raúl Enrique; Uriostegui Cordero, Dulce Lucero; Meneses Figueroa, Jazmín; Pascacio Monriel, Antonio; del Moral, Jesús; Contreras, Álvaro (Medicina e Investigación Universidad Autónoma del Estado de México, 2022)
Covid-19 was the third leading cause of death in all of 2020, but in December 2020 and the beginning of 2021, the disease suddenly spiked and briefly became the number one cause of death in the United States (u.s.), particularly among those aged 35 years or older even though as of June 30, 2021, about 66% of adults in the u.s. have received at least one Covid-19 vaccine dose. At present, there is no drug to treat Covid-19 that can reduce the morbidity and mortality significantly, which has brought great panic to the society and scientific community. Antiviral agents and immune-modulating treatments are currently being trialed. Searches were conducted in PubMed, ScienceDirect, Google Academic, LitCovid, and MedRxiv for studies published from the beginning of 2000 through April 2021 that tested the clinical uses of pidotimod. Articles were selected prioritizing randomized clinical trials, systematic reviews, and clinical practice guidelines. Research results showed that Immunotherapy proved to be an effective method for fighting against similar viral infections to Covid-19 such as sars-cov, and Middle East respiratory syndrome coronavirus (mers-cov). studies aimed to dilucidated the mechanism of action of pidotimod, as well as randomized clinical trials that evaluate the security and utility of the drug are needed. In this scenario, the administration of Pidotimod could represent a potentially innovative strategy. In conclusion, in patients with Covid-19 without pneumonia, pidotimod could be considered an option, well-tolerated, and associated with a rapid reduction of systemic symptoms of the disease